Analysis of the existence of patterns related to counter-attack and fast attack in the Spanish League 2010/2011 season. Issue 15 (10th November 2011) - Barbosa, A; Martins, N; Leitão, J; Campaniço, J; Sarmento, H
Abstract : We investigated the regular behaviour patterns in Counter-Attack (CA) and Fast Attack (FA) in the Spanish League 2010/2011 season using the instrument validated by Sarmento et al ( Medicina (Kaunas) 2010;46 ;401–7). This instrument consists in a specific notational system to study the offensive process and its variables, based on previous procedures and an exploratory phase of the study, in which we observed video images of several offensive sequences in nine games of Spanish League. To verify the occurrence of patterns, we used the software THEME 5.0, which is a professional system for detecting and analysing hidden patterns in behaviour, by performing intensive structural analysis of behavioural data. It detects complex repeated patterns that otherwise remain hidden. For the detection of the patterns, we only considered the ones repeating three times. We detected seven competed t-patterns, referring to the whole process, from recovering possession of the ball until completing the offensive process (OP) successfully. In the CA, we verified the existence of two patterns, one of which ended in goal. In the FA, we verified the existence of five patterns. Four patterns end with shot from frontal zone to goal. When analysing the patterns, we found that the area of recovery of possession is the midfield, with preponderance in the defensive midfield. In all detected patterns, the second action happens in another field zone with great impact on the opposite lateral corridor. After the ball gets to the offensive sector, there is a rapid and long change of the playing area and then the team tries to quickly end the OP. The attack ends or passes again through the corridor where it started. There is high incidence of the game in the side corridors. There was focus on strike from zone twelve, or from zone twelve to look for attack zone eleven and then terminate the action. This was a constant in all found patterns. In CA there's a pattern that ends with obtaining goal. Of the seven patterns found, both on CA and FA, the pattern that ends in a goal is the only action that ends with numerical superiority.